Effective surface preparation technique for cementitious samples in nanoindentation testing - Chow, P.; Barbhuiya, Salim (AMER SOC TESTING MATERIALS, 2017)
The nanomechanical properties of cementitious materials determined by nanoindentation largely depend on the surface roughness and intrinsicmaterial porosity of the samples. Studies have shown that high surface roughness causes an overall reduction in themeasured indentationmodulus and hardness. Therefore, it is important to reduce the surface roughness to a desirable value by means of polishing. However, polishing causes damage to the cementmatrix. Thus, the most challenging task is to obtain a reasonable surface roughness with minimumdisturbance to themicrostructure of the samples. This paper discusses an effective surface preparation technique that wouldmeet the roughness criteria for nanoindentation. With the application of Taguchimethod, the optimumparameter combinations and relative contributions of various controlling factors such as force, speed, and time of polishing were determined. A second-order response surfacemodel was developed based on signal to noise ratio to establish the relationship between the controlling factors and surface roughness. Finally, the predicted surface roughness values from both Taguchi method and response surfacemodel were compared with the experimental values of the optimized confirmation runs and a good agreement was achieved.